Stress and suffering - Ortiz Cabanillas, Pedro (1999)
We propose, in base of the conception of the fact that each human individual is a personality, that the stress must be considered also as a informational process created by natural external conditions to the society and internals, fundamentally economics of the same. Within this conception, there is no mechanical interaction between the environment and a organism, but a double determination between society and the persons. In such a way that the contradictions between the nature and the into society, and the contradictions the interior of these, they are those which determine equally contradictory situations within individual that they modify, in certain cases pathologically, the structure of the personal activity. Such changes must begin by their conscious levels, and go through the unconscious psychic levels, functional, metabolic can reach in some case the level of the genetic expression of the cells of some component, organ functional system or flesh of the person.